2011
DOI: 10.1074/jbc.m111.230375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a PreQ1 Riboswitch Aptamer in Metabolite-bound and Free States with Implications for Gene Regulation

Abstract: Riboswitches are RNA regulatory elements that govern gene expression by recognition of small molecule ligands via a high affinity aptamer domain. Molecular recognition can lead to active or attenuated gene expression states by controlling accessibility to mRNA signals necessary for transcription or translation. Key areas of inquiry focus on how an aptamer attains specificity for its effector, the extent to which the aptamer folds prior to encountering its ligand, and how ligand binding alters expression signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
242
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(267 citation statements)
references
References 64 publications
20
242
4
Order By: Relevance
“…Surface Plasmon Resonance-To analyze HIV-1 RT T/P interaction, we utilized a surface plasmon resonance technology that was previously described (26,27). In this study we used a Biacore T200 (Biacore Inc., Piscataway, NJ) and a Series S streptavidin-coated (SA) sensor chip (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Surface Plasmon Resonance-To analyze HIV-1 RT T/P interaction, we utilized a surface plasmon resonance technology that was previously described (26,27). In this study we used a Biacore T200 (Biacore Inc., Piscataway, NJ) and a Series S streptavidin-coated (SA) sensor chip (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…preQ 1 -I riboswitches have among the smallest known minimal aptamers, at 34 nt (26), but preQ 1 -II riboswitch aptamers are much larger, at ∼60 nt (27). High-resolution X-ray crystal and solution NMR structures have revealed that preQ 1 -I aptamers form H-type pseudoknots with two stems and three loops (33)(34)(35)(36). Subsequent studies detailing preQ 1 -I riboswitch dynamics and folding pathway have shown that divalent cations bind loop 1 and stabilize the bound conformation (21, 37).…”
mentioning
confidence: 99%
“…Correspondingly, the preQ 1 -II riboswitch represents a putative target for antibiotic intervention. Although preQ 1 class I (preQ 1 -I) riboswitches have been extensively investigated (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), preQ 1 class II (preQ 1 -II) riboswitches have been largely overlooked despite the fact that a different mode of ligand binding has been postulated (14).…”
mentioning
confidence: 99%